Enhanced recovery after surgery in Australia: A classic example of an evidence–practice gap - Jed Duff (Journal of Perioperative Nursing)
Enhanced recovery after surgery (ERAS) pathways – often referred to as fast-track programs – are multidisciplinary, evidence-based perioperative pathways, designed to achieve early recovery for patients undergoing major surgery. ERAS has been described as a surgical revolution because of the benefits it produces. A recent systematic review found, on average, ERAS pathways reduce length of stay by 2.3 days and case costs by $639.00; without adverse impact on mortality, adverse events, or readmissions.